Religious Thought In Indonesia An Overview - Abdul Muis Naharong (Al-Jami'ah Research Centre, 1991)
Indonesians, like other people in different parts of the world, are religious people. Different religions and beliefs, whether revealed or nonrevealed, have been embraced and practised with full conviction from time immemorial. This is because, on the one hand, being religious is a particular characteristic of man and, on the other hand, man needs religion. Men live in this world in uncertainty and dependency. This is true not only of primitive and developing societies, but of developed societies as well. In addition, there always emerge problems of destiny, suffering, and death.This fact is further aggravated by the fact that the discrepancy between expectation and actual happenings in society is quite significant It is too frequent that not good but bad men succeed. In this situation, religion is considered a way of making sense of the world which is increasingly difficult to make sense of. With religion men can patiently bear suffering and misfortune; with religion men can legitimate the good fortunes they have. Indeed,